Pedagogy model and instructional strategies in an adaptive hypermedia learning system : A proposal - Yusof, Norazah; Hamdan, Abdul Razak (2001)
This paper focuses on the pedagogy model and instructional strategies of an adaptive hypermedia learning system. SPAtH is an adaptive hypermedia learning system for teaching and learning C programming language through the World Wide Web environment. It incorporates the features of hypermedia educational system and intelligent tutoring system, which offers the freedom of exploratory learning, adapt to the learner's knowledge level, and providing the intelligent guidance and supporting the learner in acquiring knowledge. This system also promotes individualized learning. At the moment, SPAtH consists of three main components: student model, domain model and adaptive engine. Although this system lets the learner control his/her learning process and able to adapt the course materials based on the learner's academic background and knowledge states, without taking pedagogical aspect into account, better learning cannot be guaranteed. This paper discusses some pedagogical issues related in teaching and learning programming languages. It examines the Felder-Silverman learner’s learning style model, and relates these characteristics with learners whose taking computer strategies that can accommodate to these different learning styles, such as learner-content, instructor-learner and learner-learner interactions. Finally, this paper describes the proposed pedagogy model of SPAtH and how it may coorperate with the student and domain model so that effective learning can be achieved.